2017
DOI: 10.1021/acs.langmuir.7b03920
|View full text |Cite
|
Sign up to set email alerts
|

Tactoid Annealing Improves Order in Self-Assembled Cellulose Nanocrystal Films with Chiral Nematic Structures

Abstract: The self-assembly process in cellulose nanocrystal (CNC) film formation was studied as a function of evaporation time. It is known that the total evaporation time of CNC dispersions affects the structure of the film obtained, but the extension of different phases of the evaporation has not been explored. By extending the evaporation time of CNC suspensions after the onset of liquid crystallinity, the homogeneity of the resulting films could be improved as observed by polarized optical microscopy and scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 30 publications
7
105
0
Order By: Relevance
“…The films in this study were all dried at 50% relative humidity to improve reproducibility, and to ensure a longer evaporation time and, therefore, to favor chiral nematic assembly as well as coffee ring formation via EISA (Klockars et al 2018;Tran et al 2018). Otherwise, at high enough drying rates, ''kinetic trapping or arrest'' would occur for particles, limiting the formation of the coffee ring (Li et al 2016).…”
Section: Coffee Ring Development In Square Filmsmentioning
confidence: 99%
“…The films in this study were all dried at 50% relative humidity to improve reproducibility, and to ensure a longer evaporation time and, therefore, to favor chiral nematic assembly as well as coffee ring formation via EISA (Klockars et al 2018;Tran et al 2018). Otherwise, at high enough drying rates, ''kinetic trapping or arrest'' would occur for particles, limiting the formation of the coffee ring (Li et al 2016).…”
Section: Coffee Ring Development In Square Filmsmentioning
confidence: 99%
“…As the suspension evolves from biphasic to fully cholesteric upon solvent evaporation, the cholesteric domains are no longer separated by isotropic suspension but by grain boundaries with a relatively complex cholesteric reorganization and trapping of topological defects. [34][35][36][37][38] Locally, the evaporation conditions can cause additional flow in the drying suspension and lead to macroscopic accumulation of CNCs near the contact line, an example of coffee-ring effect. [18,19] At the end of that complex stage, the orientation of the cholesteric domains depends on many factors, and can present good vertical alignment through anchoring at the interfaces, or a rather disoriented distribution inherited from the initial random tactoid orientation, e.g., for thicker samples or faster solvent evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…With our chosen SOAK1 and SOAK2 conditions, we then varied the conditions for the preparation of the g‐CNC in our quest to achieve a CNC‐E with visible color. Recent work has shown that by slowing down the rate of water evaporation from the CNC suspension, a more ordered and blue‐shifted film is obtained due to a decrease in the helical pitch of the chiral nematic structure . We therefore hypothesized that we could change the pitch of the resulting CNC‐E composite by changing the helical pitch of the starting g‐CNC film.…”
Section: Methodsmentioning
confidence: 99%
“…With our chosen SOAK1 and SOAK2 conditions,wethen varied the conditions for the preparation of the g-CNC in our quest to achieve aCNC-E with visible color.Recent work has shown that by slowing down the rate of water evaporation from the CNC suspension, am ore ordered and blue-shifted film is obtained due to ad ecrease in the helical pitch of the chiral nematic structure. [20,32] We therefore hypothesized that we could change the pitch of the resulting CNC-E composite by changing the helical pitch of the starting g-CNC film. To test this hypothesis,w eu sed slow evaporation conditions to prepare the most blue-shifted g-CNC film possible and characterized it with CD spectroscopy.S low evaporation conditions produced af ilm with ar eflectance wavelength maximum of 494 nm ( Figure S6) and ah alf helical pitch of 336 nm ( Figure S7).…”
mentioning
confidence: 99%